Are process nonlinearities encoded in meandering river planform morphology?. Issue 8 (9th August 2017) - Schwenk, Jon; Foufoula‐Georgiou, Efi
Abstract: Meandering river planform evolution is driven by the interaction of local nonlinear processes and cutoff dynamics. Despite the known nonlinear dynamics governing the evolution of meandering rivers, previous attempts have found at most a weak signature of these process nonlinearities within the meander planform morphologies (form nonlinearities). In this work, we present a framework to measure form nonlinearity from centerline curvature signals and unambiguously quantify its presence in both a numerically simulated meandering river and three natural rivers. The degree of nonlinearity (DNL) metric is introduced to measure the strength of form nonlinearities embedded in the centerlines. The DNL's evolution through time is computed for annual observations over 30 years of an active, tropical meandering river and for the simulated centerline to understand how cutoffs and bend growths affect form nonlinearity. We find that although cutoffs reduce the overall form nonlinearity, they also act as a source of nonlinearity themselves by creating scales that contribute disproportionately to DNL. Key Points: Meandering river centerline geometries encode process nonlinearities The net effect of cutoffs is to reduce overall form nonlinearity, but they also act as sources of nonlinearity Form nonlinearity depends not only on the size and shape of meander bends but also on their spatial arrangement